To solve the equation for y, we need to isolate the variable y.
Starting with the given equation:
-1/5(y) + 3 = -7
First, we can subtract 3 from both sides to get rid of the constant term on the left side:
-1/5(y) = -10
Next, to get rid of the fraction, we can multiply both sides by 5:
-1(y) = -10(5)
This simplifies to:
-y = -50
Finally, we can divide both sides by -1 to solve for y:
y = 50
Therefore, the correct answer is 50.
Solve the equation for y.
−1 over 5 (y) +3 = − 7
50
-35
15
55
1 answer